Increased cerebrospinal fluid soluble TREM2 concentration in Alzheimer’s disease - Heslegrave, Amanda; Heywood, Wendy; Paterson, Ross; Magdalinou, Nadia; Svensson, Johan; Johansson, Per; Öhrfelt, Annika; Blennow, Kaj; Hardy, John; Schott, Jonathan; Mills, Kevin; Zetterberg, Henrik (Molecular neurodegeneration, 2016)
The discovery that heterozygous missense mutations in the gene encoding triggering receptor expressed on myeloid cells 2 (TREM2) are risk factors for Alzheimer's disease (AD), with only the apolipoprotein E (APOE) ε4 gene allele conferring a higher risk, has led to increased interest in immune biology in the brain. TREM2 is expressed on microglia, the resident immune cells of the brain and has been linked to phagocytotic clearance of amyloid β (Aβ) plaques. Soluble TREM2 (sTREM2) has previously been measured in cerebrospinal fluid (CSF) by ELISA but in our hands commercial kits have proved unreliable, suggesting that other methods may be required. We developed a mass spectrometry method using selected reaction monitoring for the presence of a TREM2 peptide, which can be used to quantify levels of sTREM2 in CSF. We examined CSF samples from memory clinics in Sweden and the UK. For all samples the following were available: clinical diagnosis, age, sex, and measurements of the CSF AD biomarkers Aβ42, T-tau and P-tau181. AD patients (n = 37) all met biomarker (IWG2) criteria for AD. Control individuals (n = 22) were cognitively normal without evidence for AD in CSF. We found significantly higher sTREM2 concentration in AD compared to control CSF. There were significant correlations between CSF sTREM2 and T-tau as well as P-tau181. CSF sTREM2 increase in AD was replicated in a second, independent cohort consisting of 24 AD patients and 16 healthy volunteers. CSF concentrations of sTREM2 are higher in AD than in controls, and correlate with markers of neurodegeneration. CSF sTREM2 may be used to quantify glial activation in AD.